2017
DOI: 10.1038/oncsis.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 7 is a therapeutic target in high-grade glioma

Abstract: High-grade glioma (HGG) is an incurable brain cancer. The transcriptomes of cells within HGG tumors are highly heterogeneous. This renders the tumors unresponsive or able to adapt to therapeutics targeted at single pathways, thereby causing treatment failure. To overcome this, we focused on cyclin-dependent kinase 7 (CDK7), a ubiquitously expressed molecule involved in two major drivers of HGG pathogenesis: cell cycle progression and RNA polymerase-II-based transcription. We tested the activity of THZ1, an irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…In this study, we describe a potent and selective CDK7 inhibitor occupancy. These, and published data in nonclinical models of a variety of tumor types, support the hypothesis that tumor cells have a dependency on CDK7 that is distinct from normal cells, providing a rationale for investigating CDK7 inhibitors in the clinic (12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23). SY-1365 was the first selective CDK7 inhibitor to enter clinical development and is currently being investigated as a single agent and in combination with standardof-care agents in specific groups of pateints with ovarian and breast cancer (NCT03134638).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study, we describe a potent and selective CDK7 inhibitor occupancy. These, and published data in nonclinical models of a variety of tumor types, support the hypothesis that tumor cells have a dependency on CDK7 that is distinct from normal cells, providing a rationale for investigating CDK7 inhibitors in the clinic (12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23). SY-1365 was the first selective CDK7 inhibitor to enter clinical development and is currently being investigated as a single agent and in combination with standardof-care agents in specific groups of pateints with ovarian and breast cancer (NCT03134638).…”
Section: Discussionmentioning
confidence: 71%
“…SY-1365 was the first selective CDK7 inhibitor to enter clinical development and is currently being investigated as a single agent and in combination with standardof-care agents in specific groups of pateints with ovarian and breast cancer (NCT03134638). Development of SY-1365 was motivated by the discovery and characterization of a tool compound, THZ1, which provided validation that covalent CDK7 inhibition through a cysteine residue at position 312 was a viable approach for inhibiting the growth of multiple tumor types in nonclinical models (12)(13)(14)(15)(16)(18)(19)(20)(21)(22)(23). Starting with the THZ1 scaffold, optimization of the three-dimensional shape and electron-withdrawing characteristics of the two rings linking the hinge-binding element to the covalent warhead improved the binding potency (K I ) and the deactivation rate constant (k inact ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK7 has become a potential therapeutic target, and CDK7 inhibitors have entered the clinical trial as promising methods for a variety of malignancies. THZ1 is a covalent inhibitor of CDK7, which shows strong antitumor effects in various cancers by inhibition of CDK7 [9][10][11][12][13][14][15][16] . However, the role of CDK7 and the effect of THZ1 treatment in CCA have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Kwiatkowski et al 7 reported that THZ1 can form a covalent bond by targeting a unique cysteine residue outside the cyclin-dependent kinase 7 (CDK7) kinase domain, which led to the prolonged and irreversible inactivation of CDK7. 7,[9][10][11][12][13] However, no study has been done to explore the possible effects of THZ1 on HCC yet. 8 Moreover, more and more studies illustrated that THZ1 exhibited encouraging therapeutic effects in different tumor types, such as small cell lung cancer, T-ALL, triple-negative breast cancer, ovarian cancer, and high-grade glioma.…”
mentioning
confidence: 99%